REQUIREMENTS FOR LOD IN BIM DESIGN (World Bulletin of Social Sciences, 2024)
This article focuses on the key requirements for Level of Development (LOD) in the context of BIM design. LOD represents a standardized indicator that defines the level of detail for elements in a building's digital model, encompassing both geometric (graphical) and non-geometric (informational) components. The article analyzes the classification of LOD and its roles across various stages of the project lifecycle, ranging from conceptual design (LOD 100) to asset management and operation (LOD 500). Special emphasis is placed on the general requirements for data accuracy, alignment with client expectations, and compliance with international standards such as ISO 19650. Additionally, the study explores challenges related to insufficient or excessive detailing and examines opportunities for advancements such as automation of detail validation and integration with digital twin technologies. The work highlights the importance of leveraging LOD to optimize resources, enhance communication among project stakeholders, and minimize the risks of errors in design. By addressing these aspects, LOD serves as a critical tool for improving the efficiency and effectiveness of BIMbased project execution.